A Sensitive and Selective Method for Determination of Aesculin in Cortex Fraxini by Liquid Chromatography Quadrupole Time-of-Flight Tandem Mass Spectrometry and Application in Pharmacokinetic Study. (25th September 2013) - Li, Yi; Guo, Hui; Wu, Yinying; Geng, Qianqian; Dong, Danfeng; Wu, Huili; Li, Enxiao
Abstract : A rapid and sensitive method for determining aesculin of Cortex fraxini in rat was developed using high-performance liquid chromatography (HPLC) quadrupole time-of-flight (QTOF) tandem mass (MS/MS). Rat plasma was pretreated by fourfold methanol to remove plasma proteins. Chromatographic separation was performed on a reverse phase column. A tandem mass spectrometric detection with an electrospray ionization (ESI) interface was achieved using collision-induced dissociation (CID) under positive ionization mode. The MS/MS patterns monitored were m/z 341.2716 → m/z 179.1043 for aesculin and m/z 248.3025 → m/z 120.9130 for tinidazole (internal standard). The linear range was calculated to be 10.0–1500.0 ng/mL with a detection limit of 2.0 ng/mL. The inter- and intraday accuracy and precision were within ±7.0%. Pharmacokinetic study showed that aesculin was confirmed to be a one-compartment open model. The method is believed to have good linear range, high sensitivity and recoveries, and superior analytical efficiency. It will probably be an alternative for pharmacokinetic study of aesculin.